Distribución de planta de los procesos productivos para la elaboración de calzado en la empresa Justin´s sport en el cantón Píllaro, provincia de Tungurahua - Guanin Chasi, Darwin Bladimir (2022)
The objective of this project is to design the plant distribution of the production processes for the manufacture of footwear in the Justin's Sport company, this was carried out using industrial engineering tools, such as plant distribution methods, improvement of productive capacity, in order to optimize the physical space of the new plant and reduce the long journeys of the materials, from its beginning in the cutting process to its completion in the finished product (shoes). This investigation began with the collection of information and analysis of the current distribution of the plant, in which several problems were identified due to poor distribution, there is interference between the production processes. Next, the total available area of ​​the new plant was analyzed, as well as the areas of the work stations and the routes of the materials from the beginning to the end of the process, a balance of the production line was also carried out, this to know exactly what is the number of stations necessary to produce 24 dozen footwear per day, giving us as results a cycle time of 25 minutes and 14 work stations and necessary employees, thus reducing the number of operators from 14 to 15 with the distribution proposal in the new plant and the travel distance of materials between processes is also optimized by 63%. For this, the Systematic Layout Planning (SLP) distribution method and the CORELAP software application were used. The project presents a proposal, which will allow an efficient distribution generating fewer routes of the materials, therefore it will improve the production capacity by 7% for the company Justin's Sport